ANALISIS KARAKTER TOKOH UTAMA DAN GAMBARAN KEHIDUPAN PENGARANG DALAM NOVEL DAVID COPPERFIELD KARYA CHARLES DICKENS - TELLENG, RIZKY TUNGGA TAKUMANSANG (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT The literary work is an art form shown by language. Literary works have two functions, thatâ€Ÿs, to entertain and educate. A novel, which is a longer form of a short story or a novella, is able to present the development of the characters. There are many types of characters that exist in literature, each with its own development and function. The general purpose of characters is to extend the plot. Many stories employ multiple types of characters. Every story must have main characters. This study is entitled â€œAnalisis Karakter Tokoh Utama Dan Gambaran Kehidupan Pengarang Dalam Novel David Copperfield Karya Charles Dickensâ€Â  The aims of the research is how the characters of the main character are portrayed in the novel David Copperfield. Theory of Robert Stanton (1965) about main character is used to identify and analyze the main character by the words, behavior, conversation and action. Intrinsic approach is used to analyzing the personalities for the main character and extrinsic approach is used to connect the story with other knowledge, in this case the biography of Charles Dickens.Â Â Â Â  The result of this research shows that the main character personalities are diligent, rigid, plain, hard worker, romantic, loyal and loving. Charles Dickens life are portrayed through the main character in novel, on their childhood is describe through the character words, work is describe through the character words and life on family are describe through character words, character behavior and conversation between characters. This research is expected to provide more information about the main character and connection with the life of the author to the reader. Keyword: Main character, novel David Copperfield, biography of Charles Dickens